Ketetapan Tentang Sabat Bagi Umat Israel dalam 10 Hukum Tuhan dan Relevansinya Bagi Orang Percaya Masa Kini - Kristiana Anik (Sekolah Tinggi Theologia Nazarene Indonesia, 2020)
Upon hearing the word sabbath, the tendency of many people to immediately associate it with rest, or the Adventist church's habit of worshiping on Saturday even with one of the 10 laws contained in Exodus chapter 20, even though actually the sabbath understanding is broader than all of these things. Talking about the Sabbath is also a very interesting topic, especially if it is related to the polemic that developed in the community regarding it. Not only is the notion of rest that arises in the minds of many people when they hear the word Sabbath, but it is also holy. The Sabbath is almost always associated with sanctification or holiness The fundamental question that is important to ponder is, what did God give His people for the Sabbath provision? If you look at Exodus 20: 8-11 it can be concluded that the establishment of the Sabbath reminds that God is the Creator. Whereas if you pay attention to Leviticus 23: 4-44, it is evident that the Sabbath establishment was intended so that the people of Israel could recognize that the LORD was the provider of care and maintenance. The provisions of the Sabbath are God's commands and decrees that God gave to His people. Everything determined by God is good and useful for His people. Likewise, the provisions or regulations concerning the Sabbath. The Sabbath decree teaches that God's people honor God and have a special time to worship and worship Him. God is the almighty and sovereign creator of all His creations. Sabbath also teaches care. In addition to caring for a special time to worship God, God's people must also care for others. God's people are now observing the Sabbath observance by giving special time for worship. Not in a rigid and legalistic way. Love for others also needs to be given primary consideration.